2014
DOI: 10.1002/jso.23692
|View full text |Cite
|
Sign up to set email alerts
|

Perineal reconstruction using pedicled vertical rectus abdominis myocutaneous flap (VRAM)

Abstract: The vertical rectus myocutaneous flap (VRAM) is a relatively simple and reliable technique for perineal wound reconstruction after abdominoperineal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 26 publications
2
54
1
4
Order By: Relevance
“…Amongst these studies, 118 studies were excluded for the following reasons: one animal study; four studies included other tumour types; 49 studies just reported one surgical regimen or technical material; 17 studies were reviews, letters, editorials; 11 studies lacked full text or data; nine studies were non-English articles; 27 studies were case reports. Finally, 18 studies including one RCT and 17 cohort studies published between 1948 and 2017 were included in this systematic review and meta-analysis [8,11,14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst these studies, 118 studies were excluded for the following reasons: one animal study; four studies included other tumour types; 49 studies just reported one surgical regimen or technical material; 17 studies were reviews, letters, editorials; 11 studies lacked full text or data; nine studies were non-English articles; 27 studies were case reports. Finally, 18 studies including one RCT and 17 cohort studies published between 1948 and 2017 were included in this systematic review and meta-analysis [8,11,14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Additionally, for the overall population, there were 1990 patients (12.17%) receiving preoperative radiotherapy in the primary closure group and 425 patients (27.12%) in the myocutaneous flap closure group, with a significant difference between the two groups. Among these included studies, one performed the propensity matching analysis, four matched BMI, 12 matched comorbidities and six matched preoperative radiotherapy [8,[26][27][28][29][30][31][32][33][34][36][37][38][39][40]. Nine studies on stage of cancer had the following distribution: low tumour stage (I-II) (252 cases in primary closure, 1.54%; 101 cases in myocutaneous flap closure, 6.45%) and advanced tumour stage (III-IV) (312 cases in primary closure, 1.91%; 124 cases in myocutaneous flap closure, 7.91%) [8,26,28,30,[32][33][34]38,39].…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Touny conducted a single centre RCT randomising 60 patients that received neo‐adjuvant long‐course chemoradiotherapy (CRT) to either primary closure of the perineum or vertical rectus abdominus myocutaneous (VRAM) flap reconstruction after cAPE. Significantly higher rates of wound infection, abscess, delayed healing or wound dehiscence were reported amongst the primary closure group (46.6% vs 17.2%, P = 0.015) . This result is subject to performance and detection bias due to the inability to blind the surgeon and assessors.…”
Section: Resultsmentioning
confidence: 99%
“…провели рандомизиро-ванное проспективное исследование [20]. Аналогично описанным выше, в группы сравнения (с использова-нием VRAM-лоскута и без аутопластики) вошли паци-енты, перенесшие БПЭ (все получали химиолучевую терапию); в каждую группу вошли по 30 больных.…”
Section: аутопластика раныunclassified